Understanding digital societies - Perriam, Jessamy; Carter, Simon 1960- (SAGE, in association with The Open University, 2021)
"Understanding Digital Societies provides a framework for understanding our changing, technologically shaped society and how sociology can help us make sense of it. You will be introduced to core sociological ideas and texts along with exciting global examples that shed light on how we can use sociology to understand the world around us."